Photocuring 3D printing thermoplastic elastomer material and printing method
By using materials such as styrene-butadiene-styrene ulcer segment copolymer, combined with polythiol crosslinking agent and photoinitiator, the preparation of photocured 3D printing thermoplastic elastomer is realized, and the problems of single resin types, complex synthesis and poor stability in the prior art are solved, and efficient and low-cost 3D printing materials are obtained.
Patent Information
- Application Number
- CN202510042756.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
The existing photocuring 3D printing resin has a single type, complex synthesis steps, poor stability, toxic raw materials, and the 3D printing of thermoplastic elastomers has problems such as slow printing speed and low accuracy.
The thermoplastic elastomer material is prepared by photocuring 3D printing technology by using a combination of tritoluene solution based on styrene-butadiene-styrene block copolymer, a combination of polythiol crosslinking agent, a photoinitiator and a light absorber, and the photocrosslinking of the material is achieved through thiol-ene click reaction.
The photocuring 3D printing of thermoplastic elastomers is realized, and the range of materials is expanded. The material has excellent chemical stability, no active groups, low cost, simple preparation, good printing accuracy and finished product fidelity, and high mechanical strength and elasticity.
Smart Images

Figure CN119751885A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocuring 3D printing, and in particular to a photocuring 3D printing thermoplastic elastomer material and a printing method. Background Art
[0002] Photocuring 3D printing technology is a 3D printing technology that uses photosensitive resin for additive manufacturing. Its principle is to build three-dimensional objects layer by layer through ultraviolet irradiation or other light sources to cure resin under the control of digital signals. It has the advantages of fast speed, low energy consumption, and high precision. It can prepare any structural device that is difficult to process by traditional processing methods. At present, the photosensitive resin used in this technology is mainly low-viscosity acrylic resin, and the printed products have a dense, hard and brittle network. With the promotion and application of photocuring 3D printing technology, the market demand for 3D printing consumables is becoming more and more diversified, especially the demand for elastic resin materials is increasing. Elastic resin materials can be used for 3D printing and manufacturing of soft robots, flexible electronic products, wearable devices, and microfluidic devices.
[0003] At present, the elastomer materials that can be used for photocuring 3D printing are mainly based on polyurethane-modified acrylic resins. For example, commercial photocuring 3D printing elastomer products include Carbon's EPU40, Tango Plus and Stratasys' agilus30, but the tensile strength (≤6MPa) and elongation at break (≤300%) of existing commercial products are low, and the price is relatively high. Researchers can obtain elastomer materials with higher tensile strength and elongation at break by regulating the components of polyurethane acrylate prepolymers and ink components. For example, invention patent CN116023615A discloses a synthesis method based on acrylate-terminated polyurethane prepolymers and prints polyurethane elastomers to obtain higher tensile strength. Invention patent CN117700648A discloses a photothermal dual-curing 3D printing resin material, which uses a reversibly terminated reactive terminated polyurethane prepolymer and a terminated chain extender to photocured 3D printing, and then reacts under heating conditions to form a network containing polyurethane, thereby improving the mechanical properties of the 3D printed elastomer. Invention patent CN115197375A discloses a 3D printing transparent elastomer resin, which is composed of a polyether polyurethane acrylate prepolymer, polyurethane acrylate or a reactive diluent.
[0004] However, polyurethane acrylate prepolymers often require complex synthesis steps and use highly toxic isocyanates as raw materials. In addition, the current types of light-cured 3D printing resins are relatively simple, mainly based on acrylic resins. Since acrylic resins contain more active groups, their stability is affected. For example, they are easily decomposed at high temperatures, and strong oxidants, acids, and alkalis may also cause them to degrade. Invention patent CN117736384A discloses a light-cured 3D printing elastomer material based on a multifunctional polyether acrylate prepolymer, which obtains an elastomer with higher mechanical properties, but the polyether acrylate prepolymer needs to be pre-synthesized, and the material also belongs to the acrylic resin system.
[0005] In addition, currently, 3D printing of thermoplastic elastomers mainly adopts the fused deposition manufacturing (FDM) process (CN107540799A), but this method has disadvantages such as slow printing speed, low precision, and the need for support structures when printing complex structures.
[0006] Therefore, it is of great significance to develop a new type of thermoplastic elastomer material that is easy to prepare and to perform photocuring 3D printing based on thermoplastic elastomer. Summary of the invention
[0007] The present invention aims to provide a photocurable 3D printing thermoplastic elastomer material and a printing method to address the problems of the current photocurable 3D printing resins being relatively single in type, complex in synthesis steps, poor in stability, and toxic raw materials.
[0008] In order to achieve the above technical objectives, the technical solution provided by the present invention is:
[0009] A light-cured 3D printing thermoplastic elastomer material comprises a trimethylbenzene solution of a styrene-butadiene-styrene block copolymer, a polythiol crosslinking agent, a photoinitiator, and a light absorber; wherein the concentration of the styrene-butadiene-styrene block copolymer in the trimethylbenzene solution is 1 / 5 to 1 / 7 g / mL; and the addition amounts of the polythiol crosslinking agent, the photoinitiator, and the light absorber are 2% to 10%, 1% to 2%, and 4% to 7% of the mass of the styrene-butadiene-styrene block copolymer, respectively.
[0010] Specifically, the styrene-butadiene-styrene block copolymer (SBS) can be reagent grade or industrial grade, wherein the styrene content is 30-40wt.%, the butadiene content is 70-60wt.%, the average molecular weight is 10000-200000, and the configuration is linear or star-shaped.
[0011] Preferably, a dye may be added, the amount of the dye added being 0-0.05% of the mass of the styrene-butadiene-styrene block copolymer, and the dye is selected from Sudan red and its derivatives.
[0012] Furthermore, the trimethylbenzene solution includes one or more of 1,3,5-trimethylbenzene, 1,2,3-trimethylbenzene, and 1,2,4-trimethylbenzene.
[0013] Furthermore, the polythiol crosslinking agent includes any one of a thiol-grafted polysiloxane and a small molecule polythiol crosslinking agent.
[0014] Furthermore, the mercapto-grafted polysiloxane includes a (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer and / or a (mercaptopropyl) methylsiloxane homopolymer; wherein the (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer has a molecular weight of 3000 to 8000, a viscosity of 100 to 200 cst, and a (mercaptopropyl) methylsiloxane molar ratio of 4 to 17%; the (mercaptopropyl) methylsiloxane homopolymer has a molecular weight of 4000 to 7000, and a viscosity of 75 to 150 cst.
[0015] Furthermore, the small molecule multi-thiol crosslinking agent is preferably pentaerythritol tetrakis-3-mercaptoacrylate.
[0016] Furthermore, the photoinitiator is a free radical photoinitiator, preferably one or more selected from 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO) and ethyl 2,4,6-trimethylbenzoylphosphonate (TPO-L).
[0017] Furthermore, the light absorber is preferably 2-isopropylthioxanthone (ITX).
[0018] The preparation method of the light-curing 3D printing thermoplastic elastomer material of the present invention comprises the following steps: firstly dissolving SBS in a trimethylol solvent diluent, then adding a polythiol crosslinking agent, a photoinitiator, a light absorber and / or a dye in proportion, mixing evenly to obtain the light-curing 3D printing thermoplastic elastomer material, and sealing and protecting from light for storage.
[0019] The present invention also provides a photocuring 3D printing method for photocuring 3D printing thermoplastic elastomer material, comprising the following steps:
[0020] Step 1: Pour the above materials into the material tank of the light-curing 3D printer and perform 3D printing on the sliced 3D model;
[0021] Step 2: After printing is completed, remove the sample and soak it in a dichloromethane solution for 1 to 5 minutes to remove the uncured material remaining on the surface and replace the high-boiling-point trimethylbenzene solvent. Then, place it at room temperature to evaporate or vacuum dry it to obtain the final printed sample.
[0022] Furthermore, in step 1, the printing parameters are: light source wavelength is 300-450nm, light power is 10-30mW / cm 2, the printing layer thickness is 30-150μm, the exposure time of the bottom layer is 30-50s, the exposure time of each layer is 8-12s, and the standing time is 4-6s.
[0023] The present invention also provides an application of a thermoplastic elastomer material of a styrene-butadiene-styrene block copolymer based on a mercapto-ene click reaction and a polythiol crosslinking agent in photocuring 3D printing.
[0024] The present invention has the following beneficial effects:
[0025] 1. The present invention applies the photo-crosslinking of SBS and a polythiol crosslinking agent based on a thiol-ene click reaction to photocurable 3D printing, successfully realizes the photocurable 3D printing of thermoplastic elastomers, and expands the scope of photocurable 3D printing materials.
[0026] 2. The photocurable 3D thermoplastic elastomer material disclosed in the present invention is based on the thiol-ene click reaction, can be initiated by light in an environment where oxygen exists, has no adverse reaction of free radical coupling, is a gradual polymerization reaction, and will not cause unevenness of the sample due to instantaneous rapid local reactions.
[0027] 3. The photocurable 3D thermoplastic elastomer material disclosed in the present invention does not contain active groups, has excellent chemical stability, and does not use toxic raw materials.
[0028] 4. The light-cured 3D printing thermoplastic elastomer material disclosed in the present invention has low cost, simple preparation, good printing accuracy and finished product fidelity, high mechanical strength and elasticity, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The DLP printing sample image of Example 1;
[0030] Figure 2 This is the DLP printing sample image of Example 2;
[0031] Figure 3 This is the DLP printing sample image of Example 3;
[0032] Figure 4 This is the DLP printing sample image of Example 4;
[0033] Figure 5 This is the DLP printing sample image of Example 5;
[0034] Figure 6 This is the DLP printing sample image of Example 6;
[0035] Figure 7 This is the DLP printing sample image of Example 7;
[0036] Figure 8This is the DLP printing sample image of Example 8;
[0037] Fig. 9 This is the DLP printing sample image of Example 9;
[0038] Fig.10 This is a DLP printing sample image of Example 10;
[0039] Fig.11 This is a DLP printed sample elasticity test chart of Example 10;
[0040] Fig.12 This is a graph of the tensile properties of some DLP printed samples;
[0041] Fig.13 DLP printed sample photo of Example 11;
[0042] Fig.14 DLP printed sample photo of Example 12;
[0043] Fig.15 DLP printed sample photo of Example 13;
[0044] Fig.16 DLP printing sample photo of Example 14. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0047] The raw materials can be obtained through commercial purchase.
[0048] Example 1
[0049] 5 g of SBS (styrene 30 wt.%, average Mw ~ 140000) was dissolved in 25 mL of mesitylene, 0.5 g of (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer (molecular weight 3000 ~ 4000, viscosity 100 ~ 200 cst, (mercaptopropyl) methylsiloxane molar ratio of 13 ~ 17%, SMS-142) was added, and then 0.05 g of photoinitiator TPO-L and 1.2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added. The resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0050] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0051] The tensile strength of the printed sample is 6.0 MPa and the growth at break is 526.1%.
[0052] Example 2
[0053] 5 g of SBS (30 wt. % of styrene, average Mw ~ 140000) was dissolved in 25 mL of mesitylene, 0.5 g of (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer (SMS-142) was added, and then 0.05 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0054] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0055] The tensile strength of the printed sample is 5.0 MPa and the growth at break is 639.8%.
[0056] Example 3
[0057] 5 g of SBS (30 wt. % of styrene, average Mw ~ 140000) was dissolved in 25 mL of mesitylene, 0.5 g of (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer (SMS-142) was added, and then 0.1 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0058] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0059] The tensile strength of the printed sample is 4.8 MPa and the growth at break is 502.3%.
[0060] Example 4
[0061] 5 g of SBS (30 wt. % of styrene, average Mw ~ 140000) was dissolved in 25 mL of mesitylene, 1.0 g of (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer (SMS-142) was added, and then 0.1 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0062] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0063] The tensile strength of the printed sample is 3.9 MPa and the growth at break is 485.6%.
[0064] Example 5
[0065] 5 g of SBS (30 wt. % of styrene, average Mw ~ 140000) was dissolved in 25 mL of mesitylene, 0.25 g of (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer (SMS-142) was added, and then 0.1 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0066] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0067] The tensile strength of the printed sample is 7.4 MPa and the growth at break is 903.2%.
[0068] Example 6
[0069] 5 g SBS (styrene 30 wt.%, average Mw ~ 140000) was dissolved in 25 mL of mesitylene, 0.05 g of (mercaptopropyl) methylsiloxane homopolymer (molecular weight 4000-7000, viscosity 75-150 cst, SMS-992) was added, and then 0.1 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0070] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0071] The tensile strength of the printed sample is 9.4 MPa and the growth at break is 1336.6%.
[0072] Example 7
[0073] 5 g SBS (styrene 30 wt.%, average Mw ~ 140000) was dissolved in 25 mL mesitylene, 0.1 g (mercaptopropyl) methylsiloxane homopolymer (SMS-992) was added, and then 0.1 g photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0074] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0075] The tensile strength of the printed sample is 6.7MPa and the growth at break is 879.9%.
[0076] Example 8
[0077] 5 g SBS (styrene 30 wt.%, average Mw ~ 140000) was dissolved in 25 mL mesitylene, 0.25 g (mercaptopropyl) methylsiloxane homopolymer (SMS-992) was added, and then 0.1 g photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0078] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0079] The tensile strength of the printed sample is 5.6 MPa and the growth at break is 619.9%.
[0080] Example 9
[0081] 5 g SBS (styrene 30 wt.%, average Mw ~ 140000) was dissolved in 25 mL of mesitylene, 0.1 g of pentaerythritol tetra-3-mercaptoacrylate (PTMP) was added, and then 0.1 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0082] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0083] The tensile strength of the printed sample is 7.2MPa and the growth at break is 683.2%.
[0084] Example 10
[0085] 20g SBS (styrene 30wt.%, average Mw ~ 140000) was dissolved in 100mL mesitylene, 0.4g (mercaptopropyl) methylsiloxane homopolymer (SMS-992) was added, and then 0.4g photoinitiator TPO-L, 8mL light absorber 2-isopropylthioxanthone (ITX) mesitylene solution (172mg / mL), and 0.8mL Sudan Red G mesitylene solution (5mg / mL) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material. It is a red liquid, and the rotational viscosity is tested to be 1157.7cP.
[0086] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0087] Embodiment 11
[0088] 8g SBS (styrene 30wt.%, average Mw ~ 140000) was dissolved in 48mL mesitylene, 0.16g (mercaptopropyl) methylsiloxane homopolymer (SMS-992) was added, and then 0.16g photoinitiator TPO-L and 3.2mL mesitylene solution (172mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the obtained mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material. It is a colorless and transparent liquid, and the rotational viscosity is tested to be 423.3cP.
[0089] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the rest time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -42%).
[0090] The tensile strength of the printed sample is 7.4 MPa and the growth at break is 647.5%.
[0091] Example 12
[0092] 8g SBS (styrene 30wt.%, average Mw ~ 140000) was dissolved in 56mL mesitylene, 0.16g (mercaptopropyl) methylsiloxane homopolymer (SMS-992) was added, and then 0.16g photoinitiator TPO-L and 3.2mL mesitylene solution (172mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the obtained mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material. It is a colorless and transparent liquid, and the rotational viscosity is tested to be 251.3cP.
[0093] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -44%).
[0094] The tensile strength of the printed sample is 6.6 MPa and the growth at break is 588.0%.
[0095] Embodiment 13
[0096] 5 g of industrial-grade linear SBS (styrene content of 30 wt.%) was dissolved in 25 mL of mesitylene, 0.1 g of (mercaptopropyl) methylsiloxane homopolymer (SMS-992) was added, and then 0.1 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0097] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0098] The tensile strength of the printed sample is 5.7 MPa and the growth at break is 507.0%.
[0099] Embodiment 14
[0100] 5 g of industrial-grade star-shaped SBS (styrene content of 40 wt.%) was dissolved in 25 mL of mesitylene, 0.1 g of (mercaptopropyl) methylsiloxane homopolymer (SMS-992) was added, and then 0.1 g of photoinitiator TPO-L and 2 mL of mesitylene solution (172 mg / mL) of light absorber 2-isopropylthioxanthone (ITX) were added, and the resulting mixture was mixed evenly by a planetary mixer to obtain a light-cured 3D printing thermoplastic elastomer material.
[0101] DLP printing: Pour the above printing materials into the material tank of the DLP type light-curing 3D printer, set the bottom exposure time to 40s, the layer thickness to 50μm, the exposure time for each layer to 10s, and the standing time to 5s, and print the pre-sliced 3D model. After printing, remove the molded gel sample, wash it in dichloromethane for 2 minutes, and place it in a fume hood to evaporate to obtain the final printed sample with volume shrinkage (unidirectional shrinkage rate is about -40%).
[0102] The tensile strength of the printed sample is 7.5 MPa and the growth at break is 626.9%.
[0103] The relevant test results are shown in Table 1.
[0104] Table 1 Composition and performance data of the light-cured 3D printing thermoplastic elastomer of the present invention
[0105]
[0106] From the above results, it can be seen that increasing the amount of cross-linking agent can improve the printability of the ink and reduce abnormal conditions such as deformation and breakage that occur during the printing process; however, the amount of thiol cross-linking agent used has a greater influence on the mechanical properties of the printed sample. For the same thiol cross-linking agent, increasing the amount of cross-linking agent leads to a decrease in tensile strength and elongation at break. In addition, adding a certain amount of dye can enhance the color diversity of the printed sample. Example 10 configures a red printing ink after adding Sudan Red G, and successfully prints orange-red pandas, cones, brains, teeth, hollow networks, insoles and other three-dimensional structures with a smooth surface, good molding fidelity and excellent precision. Fig.11 It can be seen that the printed hollow network structure has good elasticity, can be repeatedly pressed and quickly return to its original state; the printed dumbbell-shaped spline can be stretched several times in length without breaking; the printed insole can also be bent at will, showing good elasticity and toughness. In addition, the ink prepared with industrial-grade linear and star-shaped SBS as raw materials has good printing effect, and the printed samples have good tensile properties (Examples 13, 14), indicating that the system has good raw material universality.
[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0108] The above specific implementation methods are detailed descriptions of the present invention. It cannot be determined that the specific implementation methods of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A light-cured 3D printing thermoplastic elastomer material, characterized in that: The invention comprises a trimethylbenzene solution of a styrene-butadiene-styrene block copolymer, a multimercapto crosslinking agent, a photoinitiator and a light absorber; wherein the concentration of the styrene-butadiene-styrene block copolymer in the trimethylbenzene solution is 1 / 5 to 1 / 7 g / mL; and the addition amounts of the multimercapto crosslinking agent, the photoinitiator and the light absorber are 2% to 10%, 1% to 2% and 4% to 7% of the mass of the styrene-butadiene-styrene block copolymer respectively.
2. A light-cured 3D printing thermoplastic elastomer material according to claim 1, characterized in that: The trimethylbenzene solution includes one or more of 1,3,5-trimethylbenzene, 1,2,3-trimethylbenzene and 1,2,4-trimethylbenzene.
3. A light-cured 3D printing thermoplastic elastomer material according to claim 1, characterized in that: The polythiol crosslinking agent includes any one of a mercapto-grafted polysiloxane and a small molecule polythiol crosslinking agent.
4. A light-cured 3D printing thermoplastic elastomer material according to claim 3, characterized in that: The mercapto-grafted polysiloxane includes a (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer and / or a (mercaptopropyl) methylsiloxane homopolymer; wherein the (mercaptopropyl) methylsiloxane-dimethylsiloxane copolymer has a molecular weight of 3000 to 8000, a viscosity of 100 to 200 cst, and a (mercaptopropyl) methylsiloxane molar ratio of 4 to 17%; and the (mercaptopropyl) methylsiloxane homopolymer has a molecular weight of 4000 to 7000, and a viscosity of 75 to 150 cst.
5. A light-cured 3D printing thermoplastic elastomer material according to claim 3, characterized in that: The small molecule multi-thiol crosslinking agent is preferably pentaerythritol tetrakis-3-mercaptoacrylate.
6. A light-cured 3D printing thermoplastic elastomer material according to claim 1, characterized in that: The photoinitiator is a free radical photoinitiator, preferably one or more selected from 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO) and ethyl 2,4,6-trimethylbenzoylphosphonate (TPO-L).
7. A light-cured 3D printing thermoplastic elastomer material according to claim 1, characterized in that: The light absorber is preferably 2-isopropylthioxanthone (ITX).
8. A method for photocuring 3D printing thermoplastic elastomer material, characterized in that: The steps include: Step 1: Pour the material in right 1 into the material tank of the light-curing 3D printer, and perform 3D printing on the sliced 3D model; Step 2: After printing is completed, remove the sample and soak it in a dichloromethane solution for 1 to 5 minutes to remove the uncured material remaining on the surface and replace the high-boiling-point trimethylol solvent. Then, place it at room temperature to evaporate or vacuum dry it to obtain the final printed sample.
9. A method for photocuring 3D printing of thermoplastic elastomer material according to claim 8, characterized in that: In step 1, the printing parameters are: light source wavelength 300-450nm, light power 10-30mW / cm 2 , the printing layer thickness is 30-150μm, the exposure time of the bottom layer is 30-50s, the exposure time of each layer is 8-12s, and the standing time is 4-6s.
10. Application of a thermoplastic elastomer material of styrene-butadiene-styrene block copolymer and a polythiol crosslinking agent based on a thiol-ene click reaction in photocuring 3D printing.
Citation Information
Patent Citations
A hydrogenated styrene-b-styrene / butadiene-b-styrene copolymer, an elastomer wire material, a preparing method of the copolymer and applications of the elastomer wire material
CN107540799A
Photosensitive resin composition suitable for 3D printing transparent elastomer and preparation method thereof
CN115197375A
Acrylate-terminated polyurethane prepolymer as well as preparation method and application thereof
CN116023615A
3D printing resin material, 3D printing elastomer and preparation method thereof
CN117700648A
Elastomer capable of being used for photocuring 3D printing and preparation method thereof
CN117736384A
Cited By
Photocuring elastomer, and preparation method, use method and application thereof
CN121495048A
3D printing elastomer resin and preparation method and printing method thereof
CN122878498A